WarDriving : drive, detect, defend : a guide to wireless security - Hurley, Chris (Syngress ; Distributed by O'Reilly, 2004)
The practice of WarDriving is a combination of hobby, sociological research, and security assessment. This book is written from the inside perspective of those who have created the tools that make WarDriving possible and those who gather, analyze, and maintain data on all secured and open wireless access points in metropolitan area worldwide.